1990
DOI: 10.1073/pnas.87.16.6049
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules in the metaphase-arrested mouse oocyte turn over rapidly.

Abstract: After ovulation mammalian oocytes arrest in second meiotic metaphase. We asked whether the microtubules that comprise the meiotic spindle of mouse oocytes were stable or were undergoing rapid cycles of assembly and disassembly. Porcine brain tubulin, derivatized with biotin or x-rhodamine [5-(and -6)-carboxy-x-rhodamine], was microhijected into living oocytes. Biotinylated tubulin incorporated into the meiotic spindle to apparent equilibrium within 15 min. To assess quantitatively the rates of disassembly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…As we know, either formation or disorganization of spindles is dependent on the cooperation of motor proteins, capping proteins, MT-associated proteins and microtubulin. In the early 1990s, Gorbsky et al [44] found that MTs in the metaphase-arrested mouse oocytes could turn over rapidly, suggesting that spindles are highly dynamic. The contribution of Ca 2+ to MT depolymerization in an oxidative stress situation could be diluted due to the rapid turnover of MTs in the MII spindles, even though Ca 2+ plays a critical role in the formation of normal spindles in MI oocytes [41].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, either formation or disorganization of spindles is dependent on the cooperation of motor proteins, capping proteins, MT-associated proteins and microtubulin. In the early 1990s, Gorbsky et al [44] found that MTs in the metaphase-arrested mouse oocytes could turn over rapidly, suggesting that spindles are highly dynamic. The contribution of Ca 2+ to MT depolymerization in an oxidative stress situation could be diluted due to the rapid turnover of MTs in the MII spindles, even though Ca 2+ plays a critical role in the formation of normal spindles in MI oocytes [41].…”
Section: Discussionmentioning
confidence: 99%
“…How can plusend turnover decrease even as flux is increased? One possibility is that dynamic switching between assembly/disassembly states at plus ends contributes more to turnover than does flux (for example, Gorbsky et al, 1990). If KLP67A increases the catastrophe frequency of plus ends, then a loss of KLP67A would decrease dynamic switching, causing tubulin turnover to decrease even though flux is moving more rapidly.…”
Section: W Buster Et Almentioning
confidence: 99%
“…In the mature metaphase II (MII) oocyte, chromosomes are evenly aligned at the equatorial plate of the MII spindle. This is a dynamic structure whose microtubules undergo rapid cycles of assembly and disassembly [23]. Actin microfilaments also play an important role, providing a substrate for anchoring the meiotic spindle beneath the oocyte cortex.…”
Section: Cytoskeletonmentioning
confidence: 99%